2018
DOI: 10.1186/s12943-018-0761-9
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA XLOC_000647 suppresses progression of pancreatic cancer and decreases epithelial-mesenchymal transition-induced cell invasion by down-regulating NLRP3

Abstract: BackgroundLong non-coding RNAs (lncRNAs) play an important role in the development and progression of various tumors, including pancreatic cancer (PC). Recent studies have shown that lncRNAs can ‘act in cis’ to regulate the expression of its neighboring genes. Previously, we used lncRNAs microarray to identify a novel lncRNA termed XLOC_000647 that was down-regulated in PC tissues. However, the expression and function of XLOC_000647 in PC remain unclear.MethodsThe expression of XLOC_000647 and NLRP3 in PC spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 39 publications
2
64
0
Order By: Relevance
“…5,6 Increasing evidence has pointed out that lncRNAs are deregulated in various types of cancers and influence the progression of tumors. In recent years, many studies have shown that lncRNAs play important roles in gene regulation, transport, differentiation, dosage compensation, and protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Increasing evidence has pointed out that lncRNAs are deregulated in various types of cancers and influence the progression of tumors. In recent years, many studies have shown that lncRNAs play important roles in gene regulation, transport, differentiation, dosage compensation, and protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence shows that lncRNA exerts oncogenic or tumor suppressive role with respect to regulating cancerous biological behaviors, such as cell proliferation, migration and EMT . Accordingly, lncRNAs are increasing being identified as crucial regulators in human tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence shows that lncRNA exerts oncogenic or tumor suppressive role with respect to regulating cancerous biological behaviors, such as cell proliferation, migration and EMT. [29][30][31][32][33] Accordingly, lncRNAs are increasing being identified as crucial regulators in human tumors. Among these, antisense lncRNA is emerging as a vital participant with respect to affecting various cancerous developments, [34][35][36][37][38] In the present study, five candidates (DICER1-AS1, FAM83H-AS1, GPC3-AS1, DLX6-AS1 and SOX21-AS1) were subjected to qRT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Many NLRP3 inhibitors found to have benefits following ischemic stroke were identified as natural compounds, and further research should elucidate the relationship between molecular structure and anti-NLRP3 inflammasome function. Furthermore, several microRNAs have been demonstrated to influence the NLRP3 inflammasome pathway, including miR-22 (117), miR-132 (118), and long non-coding RNA XLOc_000647 (119). Further studies should consider the modulation of the NLRP3 inflammasome post-stroke via epigenetic approaches.…”
Section: Inhibitors Targeting the Nlrp3 Inflammasome Pathway For Ischmentioning
confidence: 99%